2000
DOI: 10.1021/la991297l
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetry Studies of Chlorpromazine Hydrochloride in Solution

Abstract: The self-association of the tranquilizer chlorpromazine hydrochloride in aqueous solution was studied. Using isothermal titration calorimetry, the critical micelle concentration and solvent-micelle interactions were evaluated as a function of temperature, ionic strength, and pH. The enthalpy of demicellization, ∆Hdemic, was directly measured from the experimental enthalpy values, which showed that the spontaneous demicellization of chlorpromazine hydrochloride is a highly endothermic process under all experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Another recent publication reported results from temperature-induced demicellization of chlorpromazine hydrochloride. However, this aggregation process seems to be significantly different from the micellar aggregation of surfactants with alkyl chains …”
Section: Introductionmentioning
confidence: 86%
“…Another recent publication reported results from temperature-induced demicellization of chlorpromazine hydrochloride. However, this aggregation process seems to be significantly different from the micellar aggregation of surfactants with alkyl chains …”
Section: Introductionmentioning
confidence: 86%
“…However, in ITC measurements, the temperature of the experiment remains unchanged while the surfactant concentration is progressively increased in the measurement cell. However, other research works (Saito et al, 2000) reported very slightly different values of DH mic for chlorpromazine hydrochloride (ionic surfactant) detemined from DSC and ITC experiments. The amplitude of the discrepancy might thus depend on the nature of the surfactant.…”
Section: Critical Micelle Concentration (Cmc) and Enthalpy Of Micellimentioning
confidence: 91%
“…The binding constant for chlorpromazine with SBE 7 -b-CD was also determined using fluorescence spectroscopy, although measurement of the binding constant was complicated by the fact that chlorpromazine exhibits self-association behaviour. [6][7][8][9][10][11] Several publications, using a range of techniques including isothermal titration calorimetry, 10 octanol-water partitioning, 8 surface tension measurements, 7 stearic acid spin label solubility measurements, 9 fluorescence 6 and UV-visible spectrophotometry 11 have reported CMCs for chlorpromazine covering a wide range (Tab. 1).…”
mentioning
confidence: 99%